Persepsi Mahasiswa Universitas Islam Negeri Sumatera Utara Terhadap Selebriti Androgini Pada Aplikasi Tik Tok - Bani Hendrio Fahrezi; Indira Fatra Deni (Program Studi Pendidikan Biologi, 2022)
This study aims to determine students' perceptions of androgynous celebrities on the Tik Tok application. Androgynous which is one of the classifications with gender role orientations: masculine and feminine. The style of androgynous dress does exist and is quite widespread in society, especially on social media. Until now, this phenomenon has received many different reactions and opinions from students and the public. The purpose of this study is to determine the understanding, reaction and perception of students to the phenomenon of androgynous clothing on Tik Tok social media. Data collection was carried out by interviews and observations. This research is a qualitative research with a descriptive method. Informant determination using purposive sampling technique with 10 informants. The results of this study state that students quite understand and know the existence of this phenomenon. College students have different perceptions and reactions to this phenomenon. There are positive, negative and also neutral.